1986
DOI: 10.1515/znc-1986-11-1231
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Procedure for the Quantitative Estimation of the Rust Fungus in Infected Plant Tissue

Abstract: A quantitative estimation of the rust fungus in infected wheat leaves was possible following enzymatic hydrolysis of the chitin and colorimetric determination of the N-acetyl-glucosamine released. The apparently complex cell wall structure of the fungal structures made it necessary, however, to use an enzyme mixture of chitinase and cellulase in order to make accessible the chitin of the cell wall for diges­tion by chitinase. In applying this method the measurement is not appreciably influenced by already form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Chitin, a cell wall constituent of most fungi, has commonly been used to measure fungal biomass (SEITZ et al 1979, RIDE andDRYSDALE 1972). The assay procedure is based on the colorimetric detection of the chitin sub-units glucosamine (RIDE and DRYSDALE 1972) or N-acetylglucosamine (WIESE et al 1986). However, both compounds have been detected in uninfected plant tissues (RIDE and DRYSDALE 1971) and, in addition, work by WHIPPS and LEWIS (1980) has shown that compounds containing hexosamine present in plant tissues may interfere with detection of fungal chitin at low infection levels.…”
mentioning
confidence: 99%
“…Chitin, a cell wall constituent of most fungi, has commonly been used to measure fungal biomass (SEITZ et al 1979, RIDE andDRYSDALE 1972). The assay procedure is based on the colorimetric detection of the chitin sub-units glucosamine (RIDE and DRYSDALE 1972) or N-acetylglucosamine (WIESE et al 1986). However, both compounds have been detected in uninfected plant tissues (RIDE and DRYSDALE 1971) and, in addition, work by WHIPPS and LEWIS (1980) has shown that compounds containing hexosamine present in plant tissues may interfere with detection of fungal chitin at low infection levels.…”
mentioning
confidence: 99%